2011
DOI: 10.18061/dsq.v31i2.1579
|View full text |Cite
|
Sign up to set email alerts
|

Review of Siebers's Disability Aesthetics

Abstract: No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Formation of the Ndiazeniumdiolate NO donors was confirmed by UV-vis spectroscopy and the appearance of a characteristic absorbance band at 253 nm ( Figure S8). 16 The resulting N-diazeniumdiolatemodified alginates possessed a broad range of NO payloads and release kinetics (Table 1), with Alg5-PAPA/NO and Alg5-DETA/NO having the fastest and shortest NO-release halflives (0.1 and 2.0 h, respectively). Overall, the NO payloads were comparable to that of previously reported water-soluble systems (0.3-0.6 μmol/mg; Table 1).…”
Section: Synthesis Of N-diazeniumdiolate-modified Biopolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…Formation of the Ndiazeniumdiolate NO donors was confirmed by UV-vis spectroscopy and the appearance of a characteristic absorbance band at 253 nm ( Figure S8). 16 The resulting N-diazeniumdiolatemodified alginates possessed a broad range of NO payloads and release kinetics (Table 1), with Alg5-PAPA/NO and Alg5-DETA/NO having the fastest and shortest NO-release halflives (0.1 and 2.0 h, respectively). Overall, the NO payloads were comparable to that of previously reported water-soluble systems (0.3-0.6 μmol/mg; Table 1).…”
Section: Synthesis Of N-diazeniumdiolate-modified Biopolymersmentioning
confidence: 99%
“…Nitric oxide (NO), an endogenously-produced free radical, holds promise as a potential therapeutic agent for treating respiratory diseases due to its broad spectrum antibacterial activity against planktonic and biofilm-based bacteria. [8][9][10][11][12][13][14][15] Present studies indicated that bacteria are unlikely to foster resistance to NO owing to the multi-mechanistic pathways (e.g., nitrosation of thiols on bacterial proteins) involved in NO's antibacterial action. 16,17 While initial studies have demonstrated the efficacy of exogenous NO in the gas form, the hazards associated with the use of pressurized cylinders and NO's high reactivity in biological media has to date limited its therapeutic utility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation